2002
DOI: 10.1080/08880010290097161
|View full text |Cite
|
Sign up to set email alerts
|

Anti-D Exerts a Very Early Response in Childhood Acute Idiopathic Thrombocytopenic Purpura

Abstract: Acute idiopathic (immune) thrombocytopenic purpura (ITP) in the pediatric population is a disease in which autoimmune features are mainly self-limited, with a reported mortality of 0.1-0.5%. Major treatment requires intravenous gammaglobulins (i.v. IgG) and corticosteroids. Recently a new globulin, anti-D, has been introduced. The authors have treated 25 children suffering from acute idiopathic thrombocytopenic purpura, with an i.v. anti-D dose of 75 microg/kg as the first treatment. Eligibility criteria inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…43,46,47 The mechanism of action of anti-D is similar to IVIg in that it decreases the clearance of platelets. More specifically, anti-D binds to the Rh + red blood cell and sensitizes it to bind to the macrophage Fc receptor and thereby promotes its clearance by the spleen.…”
Section: Anti-d Igmentioning
confidence: 98%
See 1 more Smart Citation
“…43,46,47 The mechanism of action of anti-D is similar to IVIg in that it decreases the clearance of platelets. More specifically, anti-D binds to the Rh + red blood cell and sensitizes it to bind to the macrophage Fc receptor and thereby promotes its clearance by the spleen.…”
Section: Anti-d Igmentioning
confidence: 98%
“…48 Higher doses of anti-D (50-75 mg/kg) have been shown to be the most effective at increasing the platelet count within 24 to 48 hours similar to IVIg. 46,47,49,50 Anti-D is given IV over 15 to 30 minutes and thus can be easily administered in an outpatient or emergency department setting. It has also been shown to be less costly than an equivalent dose of IVIg.…”
Section: Anti-d Igmentioning
confidence: 99%
“…Two prospective randomized trials published since the ASH and BSH guidelines claim comparable efficacy (in producing a rise in platelet count) and at least comparable safety, for standard (50 mg/kg) or higher-dose (75 mg/kg once) anti-D for newly diagnosed [25 ] or chronic [51] ITP in children. In addition, three nonrandomized trials (all level V data) have reported the use of standard and higher-dose anti-D in children with established ITP with efficacy in raising the platelet count presumed [49,57] or shown to be comparable [50] to IVIg treatment. The literature on anti-D use in ITP has been carefully reviewed [58].…”
Section: British Guidelinesmentioning
confidence: 96%
“…In high-income countries 75%-90% of cases go into complete remission irrespective of the treatment given [39][40][41] and the reported mortality in ITP is 0.1%-0.5% [23,42]. In low-income countries the remission rate within 6 months is about 44%-100%, irrespective of treatment [11,[19][20][21]43].…”
Section: Outcomementioning
confidence: 99%